Keanekaragaman dan potensi parasitoid sebagai pengendali alami ulat grayak Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) pada pertanaman jagung lahan kering: Diversity and potential of parasitoids as natural control of armyworm Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) in dryland maize crops - Mursyidin, Abdul Halim; Suana, I Wayan; Ubaidillah, Rosichon; Sutrisno, Hari (Perhimpunan Entomologi Indonesia, 2024)
Maize is an important staple food in Indonesia that is threatened by the main pest Spodoptera frugiperda (Smith), including on Sumbawa Island which is one of the centres of dryland maize production in Indonesia. Currently, S. frugiperda control still relies on synthetic insecticides because the potential of natural enemies is not widely known, especially in dryland maize crops on Sumbawa Island. This study aims to assess the potential of S. frugiperda parasitoids including diversity, evenness, dominance, richness, and parasitization rate. Samples were collected by purposive random sampling in February–May 2024 in dryland maize crops at the age of 4–6 weeks after planting on both farm that applied insecticide and farm without insecticide. A total of 30 plants with common symptoms of damage due to S. frugiperda attack in three plots each measuring 10 m × 10 m were carefully examined to collect 30 egg clusters and 30 larval individuals. The results found egg parasitoids Telenomus remus Nixon and Trichogramma nr. pretiosum Riley, larval parasitoids Exorista sp., larval-pupal parasitoids Brachymeria lasus Walker and Archytas marmoratus Townsend. We concluded that the egg parasitization was dominated by T. remus (23.54-61.22%), which has potential as a biological agent for S. frugiperda. Larval parasitization was dominated by Exorista sp. (50%), but the high parasitization rate was overshadowed by hyperparasitoid which may reduce its effectiveness as a biological agent for S. frugiperda.